2014
DOI: 10.1016/b978-0-12-405943-6.00007-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression Dynamics and Functions of Hes Factors in Development and Diseases

Abstract: Hes genes, encoding basic helix-loop-helix (HLH) transcriptional repressors, are mammalian homologues of Drosophila hairy and Enhancer of split genes, both of which are required for normal neurogenesis in Drosophila. There are seven members in the human Hes family, Hes1 to Hes7, which are expressed in many tissues and play various roles mainly in development. All Hes proteins have three conserved domains: basic HLH (bHLH), Orange, and WRPW domains. The basic region binds to target DNA sequences while the HLH r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 64 publications
1
73
0
1
Order By: Relevance
“…Consistent with this possibility, we found that Klu, Dpn and E(spl)mγ directly bind conserved sites in the 9D11 2-5 enhancer in vitro (Figures 3A and 3E; Supplementary Figures 3A-C). Dpn and E(spl)mγ are evolutionarily conserved transcriptional repressors, but how Klu regulates gene expression is less clear (Kobayashi and Kageyama, 2014; Taelman et al, 2004; Zacharioudaki et al, 2012). We generated a series of UAS transgenes that encode Klu zf (the Klu DNA-binding zinc-finger motif only), VP16::Klu zf (a constitutive transcriptional activator) or ERD::Klu zf (a constitutive transcriptional repressor).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this possibility, we found that Klu, Dpn and E(spl)mγ directly bind conserved sites in the 9D11 2-5 enhancer in vitro (Figures 3A and 3E; Supplementary Figures 3A-C). Dpn and E(spl)mγ are evolutionarily conserved transcriptional repressors, but how Klu regulates gene expression is less clear (Kobayashi and Kageyama, 2014; Taelman et al, 2004; Zacharioudaki et al, 2012). We generated a series of UAS transgenes that encode Klu zf (the Klu DNA-binding zinc-finger motif only), VP16::Klu zf (a constitutive transcriptional activator) or ERD::Klu zf (a constitutive transcriptional repressor).…”
Section: Resultsmentioning
confidence: 99%
“…Cleaved NICD has a short half-life, enabling its concentration to respond rapidly to changes in Notch activation (Fryer et al, 2004; Housden et al, 2013; Ilagan et al, 2011). Similarly, the canonical Notch target genes Hes1 and Hes5 have short mRNA and protein half-lives and their levels oscillate in many contexts (Kobayashi and Kageyama, 2014). While dynamics has been shown to play critical roles in other signaling contexts (Purvis and Lahav, 2013), it has not been systematically investigated in the Notch pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Atoh1 expression in HCs regulates the expression of genes in the Delta/Notch signaling pathway that are necessary for the development of the surrounding SCs and maintains the proper patterning of the OC (Kobayashi and Kageyama, 2014;Sprinzak et al, 2011;Yamamoto et al, 2014). Lack of the Notch ligand Jag1 results in extra rows of IHCs and the loss of OHCs (Brooker et al, 2006;Kiernan et al, 2006).…”
Section: Neurog1 Expression Alters Notch Ligand and Notch Effector Gementioning
confidence: 99%